G366(P) Impedance monitoring in paediatric gastro-oesophageal reflux disease: an evaluation of its use and clinical value. (27th April 2015) - Crook, P; Ross, A; Heuschkel, R; Zilbauer, M
Abstract : We sought to evaluate the use of combined oesophageal multichannel intraluminal impedance and pH (MII-pH) monitoring in the Paediatric department of a large tertiary hospital, and to determine whether there is added value of MII-pH monitoring beyond that of conventional pH monitoring. We conducted a retrospective study of all paediatric patients who underwent MII-pH monitoring during a two year period (01/01/2012–31/12/2013) in a large tertiary hospital. We analysed the demographics, indications for investigation and MII-pH results for each patient. We assessed the effect of anti-reflux treatment on MII-pH results and compared the relative contribution of MII data with pH data in each test. 96 studies were performed on 96 patients (mean age 3 years 8 months, range 2 months to 16 years, 55 male, 41 female). 57 studies produced interpretable results of greater than 20 h' duration. Respiratory symptoms were the most common indication for study. Patients who had taken anti-reflux medication at any point in the week prior to the study were significantly less likely to have an abnormal reflux index (RI; p < 0.05) but were not less likely to have positive symptom correlation. When considering patients off treatment in the week prior to the study, patients with an abnormal RI were found to have a significantly higher frequency of both total reflux and acid reflux events compared to those with a normal RI (p < 0.001), and were also more likely to have a positive correlation between their symptoms and impedance-detected reflux events (p < 0.01). 19 patients had both an interpretable MII-pH study and a contemporaneous oesophageal biopsy; however, no significant correlation was seen between biopsy result and any of the MII-pH indices. This study provides a comprehensive review of the use of MII-pH monitoring in a large tertiary centre. It reinforces previous literature findings that anti-reflux medication reduces oesophageal acid exposure, but does not necessarily reduce total reflux frequency or symptom correlation. The value added by MII-pH monitoring beyond that of conventional pH monitoring remains to be established. The results here support the use of RI (derived from pH monitoring) as an indicator for reflux disease in patients off treatment.